Fluorescent and magnetic properties of three complexes based on 4, 4′-(1H-1, 2, 4-triazol-1-yl)methylene-bis(benzonic acid). (1st September 2018) - Hu, Tuo-Ping; Li, Miao-Miao; Huang, Ya-Ru; Gao, Ling-Ling; Wang, Xiao-Qing; Gao, Jian-Feng; Niu, Xiao-Yan
Graphical abstract: Three coordination polymers based on 4, 4′-(1H-1, 2, 4-triazol-1-yl)methylene-bis(benzonic acid) ligands, and transition metal ions were synthesized and characterized. Complexes 1 is to be good candidates of luminescent sensors for detecting Fe 3+ . The magnetic properties of complexes 2 and 3 indicates a strong antiferromagnetic coupling among the metal centers. Abstract: Three new complexes, namely, {[Cd(TZMB)(1, 3-bimb)]·(H2 O)2 } n (1 ), {[Mn2 (TZMB)2 (1, 4-bib)0.5 (H2 O)2 ]·(H2 O)2 (DMA)} n (2 ), {[Co2 (TZMB)2 (1, 4-bib)]·(H2 O)1.5 } n (3 ), have been synthesized under hydrothermal conditions and characterized by single-crystal X-ray diffraction analysis, elemental analysis (EA), IR spectra (IR), powder X-ray diffraction (PXRD) and thermogravimetric (TG) analysis. Single X-ray diffraction analysis reveals that complex 1 is a 5-connected net 2D network with the point symbol of (4 8 ·6 2 ), complex 2 is a 3, 3, 3, 5, 9-connected net 3D framework with the point symbol of {3·4·5}{3·4 3 ·5 3 ·6 2 ·7}{3·4 5 ·5 4 ·6 11 ·7 11 ·8 3 ·9}{4·5·6}{4 2 ·6} and complex 3 is a 3, 4-connected 3D framework. The topological type of 3 is dmc (topos&RCSR.ttd) with the point symbol of (4·8 2 )(4·8 5 ). Furthermore, luminescent properties of 1 and the magnetic properties of complexes 2 and 3 were also investigated.